2001
DOI: 10.1006/geno.2001.6505
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Differentially Expressed Nucleolar TGF-β1 Target (DENTT) in Human Lung Cancer Cells That Is a New Member of the TSPY/SET/NAP-1 Superfamily

Abstract: The transforming growth factor-␤1 (TGF-␤1) responsive epithelial non-small-cell lung cancer (NSCLC) cell line NCI-H727 was used to identify potential target genes involved in TGF-␤1-mediated responses. Comparative cDNA expression patterns between cells treated with TGF-␤1 and those treated with vehicle were generated by differential mRNA display.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
57
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 70 publications
1
57
0
Order By: Relevance
“…TSPX, on the other hand, was initially considered as a TSPY-like gene, termed TSPYlike 2. It has been independently isolated in various systems and has been designated as CDA1, DENTT and CASK-interacting nucleosome assembly protein (Chai et al, 2001;Ozbun et al, 2001;Wang et al, 2004a). Recent studies on the gene organization and encoded proteins showed that its gene structure is closely related to that of TSPY, including conservation of intron-exon junctions and sequences, particularly at SET/NAP domain, but with exceptions at their amino and C termini that encode a proline-rich and acidic domain, respectively (Delbridge et al, 2004;Lau et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TSPX, on the other hand, was initially considered as a TSPY-like gene, termed TSPYlike 2. It has been independently isolated in various systems and has been designated as CDA1, DENTT and CASK-interacting nucleosome assembly protein (Chai et al, 2001;Ozbun et al, 2001;Wang et al, 2004a). Recent studies on the gene organization and encoded proteins showed that its gene structure is closely related to that of TSPY, including conservation of intron-exon junctions and sequences, particularly at SET/NAP domain, but with exceptions at their amino and C termini that encode a proline-rich and acidic domain, respectively (Delbridge et al, 2004;Lau et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…TSPY is normally expressed in male early germ cells during embryogenesis, and spermatogonia, spermatocytes and, to certain extent, the round spermatids, in adult testis (Zhang et al, 1992;Schnieders et al, 1996;Honecker et al, 2004;Lau, 2005, 2006), whereas TSPX is expressed ubiquitously in numerous cells/tissues (Ozbun et al, 2001(Ozbun et al, , 2003(Ozbun et al, , 2005Delbridge et al, 2004;Wang et al, 2004a;Lau et al, 2007). Such expression patterns suggest that TSPX could maintain a house-keeping function(s) in modulating cyclin B-CDK1 activities, and hence, cell-cycle progression, especially on G 2 /M transition, whereas TSPY has acquired various special functions pertaining to male stem germ cell proliferation and meiotic division.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously reported that p21 Cip1 interacts with the SET protein, which was firstly identified as a CAN-fusion gene in an acute undifferentiated leukemia (von Lindern et al, 1992;Adachi et al, 1994). SET belongs to a family of proteins, which includes the yeast nucleosome assembly protein NAP-I (Kawase et al, 1996), MB20 (Shen et al, 2001), Cell Division Antigen-1 (Chai et al, 2001), nucleolar transforming growth factor-b1 target (Ozbun et al, 2001), supressor of presenilin-2 (Wen et al, 2000) and testis-specific protein Y-encoded (Vogel et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…28 TSPYL2 (also known as CDA1, CINAP, or DENTT) facilitates chromatin assembly by binding to core histones in vitro and arrests cell growth. [29][30][31] Only a few studies have reported inactivation of the NAP-related protein in vitro. The downregulation of the TSPY gene in melanoma progression is caused by promoter hypermethylation.…”
mentioning
confidence: 99%